2021
DOI: 10.3390/ijms222010900
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for Non-Viral Cancer Prevention

Abstract: Cancer vaccines are a type of immune therapy that seeks to modulate the host’s immune system to induce durable and protective immune responses against cancer-related antigens. The little clinical success of therapeutic cancer vaccines is generally attributed to the immunosuppressive tumor microenvironment at late-stage diseases. The administration of cancer-preventive vaccination at early stages, such as pre-malignant lesions or even in healthy individuals at high cancer risk could increase clinical efficacy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 120 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…In this research, we concentrate on therapeutic vaccines. Previous studies have confirmed that the therapeutic vaccines promote particular antitumor immune responses ( Bayó et al, 2021 ; Faghfuri et al, 2021 ). Currently, tumor or immune cell vaccines, peptide vaccines, viral vector vaccines and DNA or RNA vaccines are the four primary categories of tumor vaccines ( Faghfuri et al, 2021 ).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this research, we concentrate on therapeutic vaccines. Previous studies have confirmed that the therapeutic vaccines promote particular antitumor immune responses ( Bayó et al, 2021 ; Faghfuri et al, 2021 ). Currently, tumor or immune cell vaccines, peptide vaccines, viral vector vaccines and DNA or RNA vaccines are the four primary categories of tumor vaccines ( Faghfuri et al, 2021 ).…”
Section: Introductionmentioning
confidence: 80%
“…Prophylactic and therapeutic vaccines are the two primary categories for developing tumor vaccines. While prophylactic tumor vaccines can be used in healthy individuals to prevent cancer-causing infections, therapeutic tumor vaccines are usually used in advanced cancers to remove cancer cells ( Bayó et al, 2021 ). In this research, we concentrate on therapeutic vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer vaccines include preventative vaccines and therapeutic vaccines. The former is mainly used in the prevention of cancer-related infections, such as hepatitis B virus vaccines and human papilloma virus (HPV) vaccines, while the latter is mainly used to treat malignancy 13 . Based on composition, tumour vaccines are divided into four groups: (1) viral vector vaccines, (2) tumour cell- and immune cell-based vaccines, (3) peptide-based vaccines, and (4) nucleic acid-based vaccines 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Tumor vaccines are mainly divided into therapeutic and preventive vaccines. Therapeutic tumor vaccines are often used in the advanced cancer to remove cancer cells, while preventive tumor vaccines can be used in healthy people to prevent cancerogenic infections (e.g., human papillomavirus or hepatitis B virus) [ 17 ]. In this study, we focused on therapeutic vaccines, which promote a specific anti-tumor immune response [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic tumor vaccines are often used in the advanced cancer to remove cancer cells, while preventive tumor vaccines can be used in healthy people to prevent cancerogenic infections (e.g., human papillomavirus or hepatitis B virus) [ 17 ]. In this study, we focused on therapeutic vaccines, which promote a specific anti-tumor immune response [ 17 , 18 ]. There are currently four main types of tumor vaccines: tumor or immune cell vaccines, peptide vaccines, viral vector vaccines, and DNA or RNA vaccines [ 18 ].…”
Section: Introductionmentioning
confidence: 99%